Makna Simbolik Dan Nilai-Nilai Buddhis Pada Tradisi Pemberian Nama Orang Jawa (Suatu Tinjauan Semiotik) - Sudarto Sudarto (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
This study aims to: (1) To describe the Njengakno ritual tradition in Tunahan Village, Keling District, Jepara Regency (2) To find out the symbolic meaning contained in the Njengakno ritual tradition in Tunahan Village, Keling District, Jepara Regency (3) To describe the Buddhist values that contained in the ritual tradition of Njengakno in Tunahan Village, Keling District, Jepara Regency This research model uses a qualitative descriptive research method using a semiotic analysis approach. Data collection techniques in this study used participatory observation, in-depth interviews with elders, religious leaders and actors involved in the naming ceremony (Njengakno). The instrument of this research was the researcher himself with interview notes, photos and writing instruments. Data analysis used is continuous categorization and comparison. The validity of the data was obtained through triangulation of sources and methods. The results of this study indicate that (1) the symbolic meaning contained in the Njengakno ritual tradition in Tunahan Village, Keling District, Jepara Regency, is the meaning of each offering presented in the njegakno ceremony, the offerings are: a) Snacks market with the meaning of fortune, health , safety to always accompany, b) white porridge and brother porridge have the meaning marked as the birth of a child, c) Kupat lepet its symbolic meaning is the philosophy of always admitting mistakes (Lepat) While lepet covers mistakes that have been forgiven, d) Wedhang buthek (Coffee) and Wedhang clear (white water) Its symbolic meaning is a symbol of a brotherhood e) Bananas have a symbolic meaning giving the meaning that all those who guard (pamomong) protect and sustain life, f) Candles, Its symbolic meaning is as a light in a life, g) Incense, The symbolic meaning of humans can give a fragrance, conditioning and give good advice good, h) Kembang (flower) The symbolic meaning of the flower is that the baby's name and family remain fragrant, i) Dekem (ingkung) the symbolic meaning of a baby who is still clean and pure as an attitude of surrender and surrender to the power of God Almighty. (3) The Buddhist values contained in the Njengakno ritual tradition in Tunahan Village, Keling District, Jepara Regency explain that Buddhist values in the njengakno ceremony tradition can be interpreted as having a positive impact, on the other hand as a form of our devotion to our ancestors in accordance with Parrita Tirokuda sutta